THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FIRM VALUE (EVIDENCE FROM INDONESIA’S BANKING INDUSTRY) - Purwaningsih, Mitha Goshita; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This research intends to collect empirical evidence regarding the effect of Good Corporate Governance on firm value. The samples consist of banks that operasionalized in Indonesia and registered on the Indonesia Stock Exchange between 2017 and 2021. The sample was selected using purposeful sampling, yielding a sample of 17 banking institutions with a total of 85 observations over a period of 5 years. To test the hypothesis, panel data regression analysis is utilized in this research. According to the findings, managerial ownership has a negative impact on firm value, institutional ownership has no impact on firm value, and audit committee and board of directors size have a positive impact on firm value. The results of this study can be a guide for investors in determining their investment decisions in terms of corporate governance.